Perizinan dan Fungsi Sanksi Administratif sebagai Sarana Pengendalian Kegiatan Bisnis pada Implementasi Masyarakat Ekonomi Asean 2015 - Haykal, Hassanain; Lasmana, Lanny (Zenit, 2015)
The agreement of cooperation among Asean Economiy Community (AEC) has a significant impact on the economy in Indonesia. Imposing AEC policies will increase the flow of services, goods, and investments. Hence, it is necessary to have State Administration Law as licences which cancontrol business activities and make them according to the law. A licence is a state instrument that is preventive juridicial, used as a means for legal administration to control the behavior and activities of society so as to fulfil the legality of law. Thus, licences can only be passed or issued solely by thegovernment as the public legal entity. By means of licences and their administrative sanctions, either in central or regional level, they are able to cotrol business activities in Indonesia by implementing AEC policies. However, the process of having a licence is not supposed to hamper the climate of investment with its complicated procedure, high costs, uncertainty of completion time, insufficient facilities and infrastructure, as well as ineffective and inefficient personnel’s performance.Keywords: licence, administrative sanctions, Asean Economy Community